2015 KSBN Award Announcement - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
This flier advertised the 2015 K-State Book Network student award. Students were asked to share their experiences related to "The Ghost Map".
Keywords: Ghost Map, The; Awards; Common reading program; Engagement; First-year experience program; Promotional materials